Empirical analysis on the impact of university teachers’ pedagogical competence on students’ satisfaction: the mediating role of learning experience - Wang, Taojing; Manda, Teja; Dai, Tingting; Hou, Wenjun (Frontiers in Education, 2025)
The main responsibility of universities is to cultivate high-quality students. The quality of student cultivation can be enhanced by improving university teachers’ pedagogical competence, and thus enhancing students’ learning experiences and satisfaction. The purpose of this study was to examine the impact of university teachers’ pedagogical competence on students’ learning experience and satisfaction, as well as the mediating effect of university students’ perception of learning experience. Structural equation modeling was employed to examine the relationships between pedagogical competency of university teachers, students’ learning experiences and classroom satisfaction, based on 569 questionnaires. The results indicate that teachers’ professional knowledge (β = 0.325, p < 0.001) and teaching skills (β = 0.155, p < 0.001) have a direct positive effect on students’ classroom satisfaction. Both factors indirectly influence satisfaction through learning experiences, with professional knowledge showing a standardized path coefficient of 0.615 (p < 0.001) on learning experiences, and teaching skills showing a coefficient of 0.335 (p < 0.001). Learning experiences have a direct effect on satisfaction with a coefficient of 0.536 (p < 0.001). Bootstrap testing confirms that the mediation effect of learning experiences is significant, with professional knowledge accounting for 50.4% of the mediation effect (total effect = 0.655, indirect effect = 0.330), and teaching skills accounting for 53.9% (total effect = 0.334, indirect effect = 0.179). The study suggests that university teachers can enhance classroom satisfaction indirectly by optimizing the depth of knowledge, teaching methods, and classroom interactions, thereby improving students’ learning experiences. This study recommends that universities strengthen training in teachers’ professional knowledge and teaching skills, and establish dynamic feedbacks mechanism for teaching outcomes. This study also offers insights for universities to enhance the various dimensions of teachers’ pedagogical competence and optimize administrative and management strategies through the learning experience and satisfaction of university students.